2018
DOI: 10.1371/journal.pone.0198508
|View full text |Cite
|
Sign up to set email alerts
|

Robo1 and vimentin regulate radiation-induced motility of human glioblastoma cells

Abstract: Glioblastoma is a primary brain tumor with a poor prognosis despite of many treatment regimens. Radiotherapy significantly prolongs patient survival and remains the most common treatment. Slit2 and Robo1 are evolutionarily conserved proteins involved in axon guidance, migration, and branching of neuronal cells. New studies have shown that Slit2 and Robo1 could play important roles in leukocyte chemotaxis and glioblastoma cell migration. Therefore, we investigated whether the Slit2/Robo1 complex has an impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Here, we report that sublethal doses of irradiation enhance the motility and invasiveness of human GSCs through HIF1α nuclear accumulation that in turn increases the cytoplasmic actin nucleator JMY. Our study is thus in line with previous reports showing that ionizing radiation promotes migration and invasion in various cancer cell lines 15 , including human glioma cell lines 5 14 , 16 , 17 , 49 . However, to our knowledge, our study is the first to show not only that human GSCs are prone to this radiation effect, but also that this is specifically linked to their stemness properties, as radiation did not induce this effect on “differentiated” glioma cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we report that sublethal doses of irradiation enhance the motility and invasiveness of human GSCs through HIF1α nuclear accumulation that in turn increases the cytoplasmic actin nucleator JMY. Our study is thus in line with previous reports showing that ionizing radiation promotes migration and invasion in various cancer cell lines 15 , including human glioma cell lines 5 14 , 16 , 17 , 49 . However, to our knowledge, our study is the first to show not only that human GSCs are prone to this radiation effect, but also that this is specifically linked to their stemness properties, as radiation did not induce this effect on “differentiated” glioma cells.…”
Section: Discussionsupporting
confidence: 93%
“…However, to our knowledge, our study is the first to show not only that human GSCs are prone to this radiation effect, but also that this is specifically linked to their stemness properties, as radiation did not induce this effect on “differentiated” glioma cells. This link may explain why we were able to use a lower dose (0.5 Gy) to enhance GSC motility compared to the dose of 1 Gy 10 – 12 or greater 5 9 , 13 , 14 , 16 , 17 required to stimulate non-stem-like human glioma cell lines.…”
Section: Discussionmentioning
confidence: 98%
“…Among the identified TYW2 targets, we selected the roundabout guidance receptor 1 (ROBO1) for further validation and study. ROBO1 was selected because it is reportedly lost in some colorectal tumors ( 30 , 31 ) and because of its proposed role as an inhibitor of cell migration and epithelial-to-mesenchymal transition (EMT) ( 32 , 33 ). We first validated the RNA expression levels observed in the RNA-seq approach by quantitative real-time RT-PCR, and found that the TYW2 unmethylated/expressing HCT-116 and SW480 cells expressed the ROBO1 transcript, whereas CRISPR/Cas9-mediated inactivation of TYW2 induced the loss of ROBO1 transcript levels ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The vimentin model (AUC: 0.854; sensitivity: 87.50%; specificity: 72.22%; accuracy: 73.80%) had good prediction performance as well. The overexpression of vimentin has been demonstrated to be associated with an increased migratory or invasive capacity of the cancer cells [59]. Therefore, vimentin is considered as a potential indicator for cancer prognosis and therapeutic target [60].…”
Section: Discussionmentioning
confidence: 99%